COLLABORATIVE GOVERNANCE DALAM PENANGANAN PEMILAHAN SAMPAH DI KOTA BANJAR - Pegi Andi Rahmawati; Ririn Yulianti; Mira Andriani (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
The waste problem in Banjar City is increasingly complex as the population increases, with waste production reaching around 50 tons per day. The handling cannot rest on the government alone, but requires structured cross-actor collaboration. This research aims to analyze the collaborative governance process in handling waste sorting in Banjar City, identify the obstacles faced, and explain the efforts made to overcome them. Using a descriptive qualitative approach with in-depth interviews, observations, and documentation methods for 12 informants consisting of the Head of the Environment Agency, Head of the Waste Division, Head of Village, Head of Governance Section, TPS/TPA manager, Head of Gici Fulfillment Service Unit (SPPG), and the community. The analytical framework refers to the model of Ansell and Gash (2008) which includes initial conditions, institutional design, facilitative leadership, and collaborative processes. The results of the research show that collaboration has run through various mechanisms such as the establishment of a waste bank, the management of TPS 3R, the Kamisama program, the signing of an MOU with SPPG, and socialization activities to the community. However, this collaboration is not optimal enough and still faces obstacles in the form of low public awareness in sorting waste, limited budget and infrastructure, and weak coordination between institutions.